Expression of microRNA-155 and human telomerase reverse transcriptase in patients with bladder cancer. Issue 1 (1st January 2020) - Abdelgawad, Ahmed; Mosbah, Ahmed; Eissa, Laila A.
ABSTRACT: Bladder cancer (BC) is the most common malignant tumor in the urinary system, with a high incidence and recurrence rate. microRNA-155 (miR-155), and human telomerase reverse transcriptase (hTERT) had a role in BC pathogenesis. In our study, we investigated the usability of miR-155, and hTERT in BC detection, muscle invasion presence, and grades of non-muscle invasive BC (NMIBC). miR-155 and hTERT were determined in urine sediment of 30 BC patients and 15 control patients with normal urologic workup by using real-time polymerase chain reaction (RT-qPCR) technique. A receiver operating characteristic (ROC) was plotted to choose the best cut-off point. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated for each marker. BC patients had lower expression of miR-155 (p= 0.005) and higher expression of hTERT (p ˂ 0.001) than control patients. Both markers had higher sensitivity than cytology for BC diagnosis (p˂ 0.001). Except for miR-155, hTERT could differentiate between NMIBC and MIBC (p˂ 0.001). miR-155 and hTERT showed no significant difference between different grades of NMIBC with p= 0.73 and p=0.07, respectively. Our results indicated that these urinary markers have the potential to be developed as non-invasive markers for BC.